Predictions based on the dsm-5 personality dimensional model and psychopathology: Differentiating borderline from affective disorders. - Henriques-Calado, J.; Gonçalves, B.; Marques, C.; Paulino, M.; Gama Marques, J.; Grácio, J.; Pires, R. (20th WPA World Congress of Psychiatry, 2021)
Objectives Previous research highlights that borderline personality disorder (PD) and affective disorders have clinical features in common which often make their differential diagnosis difficult. Although there is a growing body of literature on the alternative dimensional classification for personality disorders in DSM-5, its discriminative characteristics between clinical samples are still understudied. This study seeks to identify the best set of predictors that differentiate borderline PD from bipolar disorder and major depression, based on DSM-5 maladaptive personality traits/facets and psychopathological symptoms. Methods A cross-sectional study of three psychiatric samples: 1) Borderline PD sample of 63 participants (Mage=40.32 years; Mschooling=9 years), mainly male (55.6%); 2) Bipolar disorder sample of 65 participants (Mage=46.49 years; Mschooling=12 years), mainly female (60%); 3) Major depression sample of 89 participants (Mage=47.80 years; Mschooling=12 years), mainly female (51.6%). Self-reported assessment: PID-5; BSI. Two logistic regression analyses were computed. Results The model that predicted the presence of borderline PD versus bipolar disorder, accounting for 33% of the variance: PID-5 restricted affectivity (odds ratios (OR): 3.28), PID-5 rigid perfectionism (OR: 3.14), BSI phobic anxiety (OR: 2.57). In turn, the model that predicted the presence of borderline PD versus major depression, accounting for 48% of the variance: PID-5 unusual beliefs & experiences (OR: 4.53), PID-5 impulsivity (OR: 3.19), BSI obsession-compulsion (OR: 2.72), BSI hostility (OR: 2.86). Conclusions Findings support the DSM-5 dimensional model criteria B maladaptive traits for differentiating borderline PD from affective disorders. Furthermore, the analyses reinforce the joint use of symptom-related pathological functioning within a spectra with overlapping features.